P.044 Quality of life in children with epilepsy treated with the low glycemic index diet – a pilot study. (June 2019) - Boles, S; Webster, R; Parnel, S; Murray, J; Ieradi, S; Sell, E; Pohl, D
Abstract : Background: The classic ketogenic diet is the main non-pharmacological treatment for refractory epilepsy; however, adherence is often challenging. The low glycemic index diet (LGID) is less strict, almost equally effective, and associated with improved adherence. Little is known about the quality of life of children treated with LGID. The objective of this study was to explore changes in the quality of life of children with epilepsy transitioning to the LGID. Methods: Patients on LGID and their parents filled out Pediatric Quality of Life Epilepsy Module questionnaires; one while being on the LGID, and one retrospectively for the time prior to starting the LGID. Results: Data was collected from five children ages 3-13 and their parents. Complete seizure control was seen in two children, >50% seizure reduction in one, and no change in two children. Parental reported quality of life while on the LGID increased with two participants but decreased in all child self reports. Conclusions: Although the LGID led to improved seizure control in three out of five patients, the child-reported quality of life decreased in all children. Larger prospective studies are warranted to reliably assess the impact of the LGID on the quality of life in children with epilepsy.